Impact of Permanent Post-thyroidectomy Hypoparathyroidism on Self-evaluation of Quality of Life and Voice: Results From the National QoL-Hypopara Study. Issue 5 (November 2021) - Frey, Samuel; Figueres, Lucile; Pattou, François; Le Bras, Maëlle; Caillard, Cécile; Mathonnet, Muriel; Hamy, Antoine; Brunaud, Laurent; Lifante, Jean-Christophe; Trésallet, Christophe; Sebag, Frédéric; Menegaux, Fabrice; et al.
Abstract : Objective: The aim of this study was to compare the quality of life (mental health) and voice in patients with or without permanent hypoparathyroidism after total thyroidectomy. Summary Background Data: Permanent hypoparathyroidism is an underestimated complication of thyroid surgery owing to suppression of parathormone secretion. Few studies have evaluated the consequences of hypoparathyroidism on quality of life and none has studied its effects on voice. Methods: The QoL-hypopara study (ClinicalTrial.gov NCT04053647) was a national observational study. Adult thyroidectomized patients were included between January and June 2020. A serum parathormone level <15 pg/mL >6 months after surgery defined permanent hypoparathyroidism. Patients answered the MOS-36-item short-form health (SF-36), the Voice Handicap Index (VHI) surveys, and a list of questions regarding their symptoms. Results: A total of 141 patients were included, 45 with permanent hypoparathyroidism. The median period between thyroid surgery and the questionnaire was 6 (Q1-Q3 4–11) and 4 (4–5) years in hypoparathyroid patients and controls respectively. Hypoparathyroid patients presented a reduced median mental score ratio (SF-36) [0.88 (Q1–Q3 0.63–1.01) vs 1.04 (0.82–1.13), P = 0.003] and a lower voice quality (incidence rate ratio for total VHI 1.83-fold higher, P < 0.001). In multivariable analysis, hypoparathyroidism [−0.17 (95% confidence interval −0.28 to −0.07), P = 0.002], but not age, female sex, thyroid cancer, or abnormal TSH level, was associated with the reduced mental score ratio. Myalgia, joint pain, paresthesia, tetany, anxiety attack, and exhaustion were the most common symptoms among hypoparathyroid patients (>50%). Conclusions: Hypoparathyroid patients present significantly impaired quality of life, lower voice quality, and frequent symptoms. These results reinforce the importance of preventing this complication. Abstract : Supplemental Digital Content is available in the text